2012
DOI: 10.1038/ejhg.2012.268
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of SLX4 loss-of-function mutations in non-BRCA1/2 breast and/or ovarian cancer families

Abstract: Fanconi anemia is a genetically heterogeneous autosomal recessive disorder characterized by development abnormalities, bone marrow failure, and childhood cancers. Compelling evidence indicates a common genetic basis for FA and breast/ovarian cancer susceptibility. Recently, biallelic germ-line mutations in SLX4 have been demonstrated to cause a previously unknown FA subtype (FA-P). We address the role of SLX4/FANCP in breast/ovarian cancer susceptibility by conducting a comprehensive mutation scanning in 486 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…We found that L530A amino acid change (#7, Table 2) abolished the interaction, but Y546A (#6) or L550A (#3), as well as E532A (#2), did not affect appreciably the interaction. Interestingly, Y546C (rs150547487) was detected in the SLX4 mutation screening of non-BRCA1/2-mutated breast cancer families [23] and is recorded as a global minor allele with a frequency of 0.0038 (dbSNP, NCBI Resources). The Y546C mutation (#5) did not significantly impair the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…We found that L530A amino acid change (#7, Table 2) abolished the interaction, but Y546A (#6) or L550A (#3), as well as E532A (#2), did not affect appreciably the interaction. Interestingly, Y546C (rs150547487) was detected in the SLX4 mutation screening of non-BRCA1/2-mutated breast cancer families [23] and is recorded as a global minor allele with a frequency of 0.0038 (dbSNP, NCBI Resources). The Y546C mutation (#5) did not significantly impair the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…2 Mutations in the RAD51C/FANCO gene were originally found in breast/ovarian cancer families. 8 [10][11][12][13] However, subsequent analyses allowed the identification of (i) three unique SLX4-truncating mutations, [14][15][16] indicating these mutations are very rare in familial cases, and (ii) a nonsense mutation in FANCM, whose frequency in cases was, however, not significantly higher than that in controls. 17 Finally, deleterious mutations in the FA gene XRCC2 were detected in families with breast cancer ascertained mainly in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…A dominant negative mutation has not been observed in the >2500 index cases from hereditary breast cancer families which have been analyzed for deleterious mutations in the coding sequences of the SLX4 gene in eight studies . In one of these studies, the LD structure of the region was detected and two selected variants were tested for association in larger cohorts.…”
Section: Discussionmentioning
confidence: 99%